KOMPETENSI KARYAWAN BUTLER DI PADMA HOTEL BANDUNG - Antonius Iskandar; Michael Prana Yoga Siahaan (Akademi Pariwisata NHI Bandung, 2023)
This study aimed to identify and analyzed the state of Competence For Butler Service At Padma Hotel Bandung. This research was conducted at Padma Hotel Bandung with a population of as many as 1 Front Office Manager and 11 Butler Section. The method used is descriptive analysis method using continum analysis. The result of this study are as follows : 1) The state of Butler Knowledge at Padma Hotel Bandung it is Good categories, with an average score of 262,00; 2) The state of Skill it is Good categories, with an average score of 203,00; 3) The state of Attitude it is Average categories, with an average score of 221,00. The Result of analysis are as follows: 1) Knowledge it is Fair categories; 2) Komitmen it is Fine categories; 3) Bentuk Pelaksanaan Mengikat is Fair categories; 4) Perananan Seluruh Unsur is Fine categories; 5) Penyempurnaan is Fair categories; 6) Pendokumentasian is Fair categories. The conclusion of this study is shown to identify and analyzed implementation of Standard Operating Procedures For Waiters Service At Feast Restaurant Sheraton Bandung Hotel & Towers.